Time Management to Reduce Delays in Middle School Students - Aini Nadhifah Purnamasari; Suroso Suroso (International Consortium of Education and Culture Research Studies, 2020)
This study aimed to determine the effectiveness of providing time management assistance. to reduce the intensity of tardiness in 7th grade female students. This research is an experimental study with a single subject research. Interventions were carried out on research subjects and parents. Intervention by accompanying the subject in managing the time of daily activities clearly and in writing, while the subject of intervention in parents is psychoeducation. Interventions conducted on the subject were done in 4 sessions with each session carried out for 60 minutes where in the first session the subject was given an explanation of the importance of time management, in the second session the subject was asked to detail the important daily activities and must be carried out and determine the time at each activity, in the third session the subjects were asked to evaluate related matters that did not support the fulfillment of the specified time management and the things that might be done to keep doing activities in accordance with the time specified and for the fourth session the subjects were asked to evaluate the entire intervention process and conclude with regard to its effects. The intervention that was carried out to parents was carried out 1 time with a duration of 30 minutes. The result of the intervention is that the research subject can manage the time of daily activities more clearly and in writing so that he can follow the set time. In the subject's parents, the subject's mother understood more about the subject's problems and needs so that the parents paid more attention to the subject and determined someone to bring the subject to school at the designated time. From the interventions carried out, there are changes in the way of thinking and attitudes towards the subject and parents of the subject which are expected to reduce the intensity of the subject's lateness to school.